REPRESENTASI SOSIAL TOKOH ALYA HAGIA SHOFIA DALAM NOVEL LAUT TENGAH KARYA BERLIANA KIMBERLY - Alpan Ahmadi; Riadatul Jannah (Lembaga Berugak Baca, 2025)
This study examines the social representation of the character Alya Hagia Shofia in Laut Tengah, a novel by Berliana Kimberly, through the perspectives of sociology of literature and feminist literary criticism. A qualitative descriptive method is employed by analyzing narrative passages, dialogues, and inner monologues of the main character. The findings indicate that Alya is represented as a woman positioned in subordination due to patriarchal social structures, domestic violence, and economic dependency. At the same time, Alya is portrayed as a reflective subject with educational aspirations and religious consciousness. This representation reveals an ambivalence between resignation and symbolic resistance in responding to gender inequality. Laut Tengah reflects the social realities of contemporary Indonesian women who live within ongoing negotiations between traditional values, religiosity, and modernity. Therefore, this work contributes to the discourse on popular Indonesian literature as a medium of social critique concerning gender power relations.